1995
DOI: 10.1029/95jb01863
|View full text |Cite
|
Sign up to set email alerts
|

Observations of regional phase propagation across the Tibetan Plateau

Abstract: We present observations of regional phase velocity and propagation characteristics using data recorded during a 1‐year deployment of broadband digital seismic stations across the central Tibetan Plateau along the Qinghai‐Tibet highway from Golmud to Lhasa. Previous seismological studies within this region have had to rely on earthquakes recorded almost exclusively at stations outside of the plateau. We have the opportunity to study numerous source‐receiver paths confined entirely within the Tibetan Plateau. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
102
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(126 citation statements)
references
References 26 publications
21
102
1
1
Order By: Relevance
“…Direct phase and coda amplitude measurements, using modern digital seismic instruments, have confirmed that attenuation in the western United States is significantly higher than in the eastern United States [Mitchell, 1975[Mitchell, , 1981Frankel et al, 1990;Benz et al, 1997]. In fact, global observations confirm that S-wave coda and Lg attenuation is higher for regions with active tectonism than for stable continental interiors [Aki, 1980a[Aki, , 1980bBenz et al, 1997;McNamara et al, 1996]. This study focuses on the frequencydependence of the Lg wave quality-factor in south-central Alaska.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Direct phase and coda amplitude measurements, using modern digital seismic instruments, have confirmed that attenuation in the western United States is significantly higher than in the eastern United States [Mitchell, 1975[Mitchell, , 1981Frankel et al, 1990;Benz et al, 1997]. In fact, global observations confirm that S-wave coda and Lg attenuation is higher for regions with active tectonism than for stable continental interiors [Aki, 1980a[Aki, , 1980bBenz et al, 1997;McNamara et al, 1996]. This study focuses on the frequencydependence of the Lg wave quality-factor in south-central Alaska.…”
Section: Introductionsupporting
confidence: 53%
“…The frequency-dependent quality factor, Q(/), is commonly modeled using a power law of the form: [Frankel and Wennerberg, 1987]; however, good correlation between coda Q and Lg Q estimates have been observed in regions such as the Tibetan Plateau [Xie and Mitchell, 1991;McNamara et al, 1996]. This study presents the first estimate of Lg frequency dependent Q in south-central Alaska using broadband instrumentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As most of the path of P n for the shot records is within the 'No-S n -zone' previously mapped (Barazangi and Ni, 1982;McNamara et al, 1995), one can speculate that the absence of P n on the INDEPTH III shot records is related to the absence of S npropagation in the northern part of the INDEPTH III array. By introducing unusually strong attenuation into the sub-Moho layers of the synthetic models, we found that a P-wave quality factor Q P of f 180 -340 (corresponding to Q A f 80 -150) could explain the absence of high frequency P n , while leaving the lower-frequency P n phase from the earthquakes strong enough to be detected over the ranges considered in this paper.…”
Section: Attenuation Anisotropy and Temperaturementioning
confidence: 99%
“…Rapine et al (2003) find a low lower-crustal S-wave velocities and the absence of an S velocity gradient in the mantle beneath northern Tibet from dispersion studies. McNamara et al (1995), studying S n regionally, map a large elliptically formed attenuation area in central Tibet, mainly in the Changtang Block. Quaternary volcanism and our unusually low P-velocities in the lower crust and upper mantle from wide-angle and refraction studies, and P n tomography (McNamara et al, 1997;Haines et al, 2003) fit perfectly into the concept of a hot, attenuating and weak, possibly anisotropic and easterly escaping, lithosphere.…”
Section: Attenuation Anisotropy and Temperaturementioning
confidence: 99%